Analyzing the spatial pattern of potential mother trees in SISFEC by using GIS-based pattern analysis - Yaacob, Siti Aisyah (2016)
Mother tree is the parent tree that produces seedlings and saplings to ensure the sustainability of a forest production in an area. The sustainability of timber trees with good traits is important to ensure the quality of timbers. Generally, the distribution and pattern of mother trees are recorded aspatially without consisting the spatial information and tabular data of the mother trees. Therefore, this study was conducted in order to assess the distribution and pattern of the potential mother trees existed in Sultan Idris Shah Forestry Education Centre (SISFEC) by using Geographical Information System (GIS) technology. This study had been conducted in SISFEC, located in Puchong. The purposes of this study are to identify the potential mother trees in SISFEC based on phenology observation and to analyse the spatial distribution of mother trees in SISFEC by using spatial pattern analysis of GIS. Existing mother trees in SISFEC are searched and identified using the phenology observation and the location of the mother trees are marked with Global Positioning System (GPS). The scientific name, local name, diameter breast height (DBH), tree height and canopy percentage are recorded into the mother tree form made. The data are then analysed with average nearest neighbour of spatial analysis. The mother tree patterns that existed in SISFEC are dispersed and random pattern. Dispersed pattern are vastly found in flat area meanwhile the random pattern is available at the slope and steep area. There are four familia of mother trees identified in SISFEC which are Dipterocarpaceae, Apocynaceae, Thymelaeaceae and Sterculiaceae. The total number of mother trees recorded in this study is 171 with 19 species. As for conclusion, the most abundant species of mother trees recorded during this study is from Dipterocarpaceae family with the total of 163 trees. Meanwhile, the least species of mother tree in this study is from Apocynaceae with only 1 standing mother tree.